Neurologic Manifestations of Influenza A(H3N2) Infection in Children During the 2016–2017 Season. (27th December 2018) - Rao, Suchitra; Martin, Jan; Ahearn, M Alex; Osborne, Christina; Moss, Angela; Dempsey, Amanda; Dominguez, Samuel R; Weinberg, Adriana; Messacar, Kevin B
Abstract: Among 182 children with influenza infection in 2016–2017, 18% had neurologic manifestations of influenza (NMI), including seizures and encephalopathy; 85% of these children were infected with the H3N2 strain. Children with NMI had 3.5-times-higher odds of having a neurologic comorbidity than those without NMI and a 10-fold increased odds of hospitalization.